Subcellular structural plasticity caused by the absence of the fast Ca2+ buffer calbindin D-28k in recurrent collaterals of cerebellar Purkinje neurons - Orduz, David; Boom, Alain; Gall, David; Brion, Jean-Pierre; Schiffmann, Serge N.; Schwaller, Beat (Frontiers in Cellular Neuroscience, 2014)
Purkinje cells (PC) control spike timing of neighboring PC by their recurrent axon collaterals. These synapses underlie fast cerebellar oscillations and are characterized by a strong facilitation within a time window of <20 ms during paired-pulse protocols. PC express high levels of the fast Ca2+ buffer protein calbindin D-28k (CB). As expected from the absence of a fast Ca2+ buffer, presynaptic action potential-evoked [Ca2+]i transients were previously shown to be bigger in PC boutons of young (second postnatal week) CB-/- mice, yet IPSC mean amplitudes remained unaltered in connected CB-/- PC. Since PC spine morphology is altered in adult CB-/- mice (longer necks, larger spine head volume), we summoned that morphological compensation/adaptation mechanisms might also be induced in CB-/- PC axon collaterals including boutons. In these mice, biocytin-filled PC reconstructions revealed that the number of axonal varicosities per PC axon collateral was augmented, mostly confined to the granule cell layer. Additionally, the volume of individual boutons was increased, evidenced from z-stacks of confocal images. EM analysis of PC-PC synapses revealed an enhancement in active zone (AZ) length by approximately 23%, paralleled by a higher number of docked vesicles per AZ in CB-/- boutons. Moreover, synaptic cleft width was larger in CB-/- (23.8 ± 0.43 nm) compared to wild type (21.17 ± 0.39 nm) synapses. We propose that the morphological changes, i.e. the larger bouton volume, the enhanced AZ length and the higher number of docked vesicles, in combination with the increase in synaptic cleft width likely modifies the GABA release properties at this synapse in CB-/- mice. We view these changes as adaptation/homeostatic mechanisms to likely maintain (preserve) characteristics of synaptic transmission in the absence of the fast Ca2+ buffer CB. Our study provides further evidence on the functioning of the Ca2+ homeostasome.